Urbanization, mainly rurality, but not altitude is associated with dyslipidemia profiles - Lazo-Porras M. (2017)
Geographical and environmental features such as urbanization and altitude may influence individual's lipid profiles because of the diversity of human-environment interactions including lifestyles.